Identification of a 1, 274‐bp promoter of a Musa acuminata L. aquaporin gene (MaPIP1;1) which confers salinity stress inducibility in transgenic Arabidopsis. (7th January 2021) - Song, Shun; Ma, Funing; Huang, Dongmei; Wu, Bin; Ma, Chaozhi; Li, Jingyang; Li, Yujia; Wei, Qing; Sun, Qiurong; Wang, Wenquan; Xu, Yi
Abstract: Salt stress will seriously influence alt stress in banana ( Musa L.) induces MaPIP1;1, which enhances the salt resistance of transgenic Arabidopsis. The promoter pMaPIP1;1, located 13, 62 bp upstream of the transcriptional start site, was isolated from the banana genome, and four pMaPIP1;1::GUS fusion constructs namely M‐P1, M‐P2, M‐P3, and M‐P4 were used to transform into Arabidopsis. In this work, in order to functionally verify the promoter responds to high salt stress, we used NaCl treatment for simulating salt terms. NaCl treatment is responded to by four transformants. M‐P2 (−1, 274 bp to −1) showed the highest transcriptional activity among all transgenic Arabidopsis transformants. This area of the promoter endows high glucuronidase (GUS) enzyme activity according to NaCl treatment. These results will help us understand the transcriptional regulatory of MaPIP1;1, and promoter fragment M‐P2 will be an ideal candidate for overexpression of salt response genes to increase plant resistance. Core Ideas: MaPIP1;1 was induced by high salt stress in bananas and enhanced the salt tolerance of transgenic Arabidopsis. A 1, 274‐bp region of the promoter confers the highest salinity inducibility in transgenic Arabidopsis. The promoter fragment M‐P2 can be an ideal candidate for increasing the salt tolerance of plants.